PERSEPSI TOKOH ISLAM DI KOTA PADANG TENTANG POLIGAMI DALAM ASPEK MASLAHAH - Hayattullah, Kumaini; Zulkarnaini, Zulkarnaini; Bahar, Muchlis (UIN Imam Bonjol Padang, 2020)
Polygamy is a man who has a wife more than one up to four people. In Islamic view, polygamy can be done if it meets the recuirements that are clearly mentioned in the Qur’an, that is being able to be fair. The fair referred includes several parts, namely: fair in the shared time, fair in living, fair in the place of recidence and fair in the cost of the child. Rasulullah’s polygamy is different from the polygamy phenomena that we face today. The practice of the prophet’s polygamy is not based on biological needs, but there are several considerations including wanting to honor the window, raising the degree of windows and women who offer herself to be married. In the present, polygamy is based solely on biological needs, and lose the element of justice in it.